Perilaku Pencegahan COVID-19 pada Klien Kontak Erat - Riskiyanto, Azi; Indarjo, Sofwan (Indonesian Journal of Public Health and Nutrition, 2021)
Background: Someone with a history of close contact has a high risk of being infected with COVID-19, based on research has a proportion of 42% to be infected. At the Kajen II Health Center, it showed that 77 close contacts, 31 of them were declared infected with COVID-19. This study aims to analyze factors related to COVID-19 prevention behavior in close contacts. Methods: This type of research uses an analytical survey with a cross-sectional design. The population in this study was 77 close contacts and a sample of 47 respondents, with purposive sampling technique. Instrument using a questionnaire, data analyzed used chi square test and logistic regression. Results: There is a relationship between geder (p = 0,024), knowledge (p = 0,013), perceived suspectibility (p = 0,020), perceived bariers (p = 0,000), self-efficacy (p = 0,000), family support (p = 0,003), and information access (p = 0,002). Strong contributing factors are information access (OR = 15,957), perceived bariers (OR = 33,842), dan self-efficacy (OR = 25,696). Conclusion: There is a relationship between gender, knowledge, perception suspectibility, family support, where access to information, perceived barriers and self-efficacy are variables that are strongly related to COVID-19 prevention behavior in close client contacts.